Molecular analysis of NS1 gene of Indian protoparvoviruses - KAUR, PARMINDER; MUKHOPADHYAY, CHANDRA SHEKHAR; DEKA, DIPAK; MALIK, YASHPAL SINGH (The Indian Journal of Animal Sciences, 2023)
Porcine parvovirus (PPV) is a predominant infectious agent responsible for infertility in pigs. Globally, it leads to colossal economic loss to the pig rearing communities, especially in the developing countries. The nonstructural gene 1 (NS1) of PPV is responsible for the virus replication, transcription regulation and cytotoxicity. Variations in the NS1 gene could cause increased virulence of the virus and the enhanced virulence raises concern about the effectiveness of the PPV vaccines against newly emerging strains. So, in the present study, we collected 84 samples from different regions of Punjab and Guwahati (Assam) during 2019-2022. Out of 84 samples, 12 samples were positive for PPV-1. The NS1 gene was cloned and sequenced followed by analysis of Indian PPV-1 isolates to understand its evolutionary background, level of divergence and nucleotide/amino acid substitutions. The findings revealed that Indian PPV-1 isolates exhibit nucleotide substitutions with high percent sequence identity. Pairwise distance matrix values of the NS1 gene revealed that local PPV-1 isolates showed maximum divergence from sequences of Brazil, China, Korea and Germany. Furthermore, selection pressure analysis revealed that all the isolates were under positive selection. The findings of the current study warrant whole genome analysis of circulating PPVs in India to identify a putative vaccine strain for combating emerging PPVs.